Pol Pot the journey to the killing fields - William, Andrew ([Australia] : BBC, 2005)
There have been many ruthless dictators in the last century, who have killed millions in their quest for power, but few have managed to inflict such enormous damage on one small country. During Pol Pot's four-year reign of Cambodia he exterminated nearly a third of his own people. Between one and three million Cambodians died during the three years, eight months and 20 days of Pol Pot's rule.
Film editor, Fred Hart ; editor, John Farren
Narrator: Michael Praed ; voice of Pol Pot, Kenneth Cranham
dvd format
Keywords: Pol Pot; Cambodia -- Politics and government